Students' Perception Toward the Use of Geschool in Learning English - Annisa Nur Umatil Iqbal; Nur Rosita (Journal of English Language Teaching, 2022)
The focus of learning had changed from face-to-face learning to online learning because of the covid-19 pandemic that happened in the beginning of March 2020 in Indonesia. Geschool was one of the alternative ways which was used for online learning. This study aimed to find out students’ perception toward the use of Geschool in English learning which was relevant with the lesson delivery, accessibility, media, features and materials used, and personal factors. The design of the research was conducted by using the descriptive research with a quantitative and qualitative approach. The population of this reseach was eighth grade students of of SMPN 1 Gunung Talang academic year 2021/2022 consisted of 176 students. The sampling was 136 students consented to participate in this study and 2 participants were interviewed per each class. The result was the students had relatively negative perceptions toward the use Geschool in learning English. The students mostly got confused and did not understand the materials because teachers barely gave further explanations. They also cannot enjoy the learning. The students were easy to access the material and assignment given in Geschool. However, they cannot get more access to the references or reading materials. Unfamiliar with the Geschool was also one of the problems students face and it took time to master the application. The students were also less-motivated and felt lazy learning English toward Geschool.